Tinjauan Yuridis Perjanjian Waralaba Menurut Hukum Positif di Indonesia - claudia, jean; Urbanisasi, Urbanisasi (Faculty of Law, Diponegoro University, 2023)
A franchise is a form of business partnership between two parties known as the franchisor and the franchisee. During the partnership period, the franchisee has the right to use the franchise's trademarks, business systems, technical assistance, and training, as well as other important aspects related to the business. In fact, a franchise agreement has a fairly high level of complexity because it involves many aspects and certain details that must be considered by both parties. The relationship between franchising and default is very close because the implementation of the contract is difficult when there is disagreement about the rights and obligations of each party in the franchise cooperation. If there is a violation on the part of the franchisor, the franchisor has the potential to take legal action. Such violations may include non-compliance with or violation of established procedures in promoting and disseminating the franchise mark, as well as non-compliance with the rules set by the franchisor in managing the business. By conducting this review, it is hoped that it will provide a firmer and more thorough understanding of franchise contracts from the perspective of positive law in Indonesia, so that all parties involved in the agreement can understand their rights and responsibilities and avoid possible legal problems in the future.